The philosopher in the valley : Alex Karp, Palantir, and the rise of the surveillance state - Steinberger, Michael (Avid Reader Press, 2025)
"Palantir builds data integration software: its technology ingests vast quantities of information and quickly identifies patterns, trends, and connections that might elude the human eye. Founded in 2003 to help the US government in the war on terrorism--an early investor was the CIA--Palantir is now a $400 billion global colossus whose software is used by major intelligence services (including the Mossad), the US military, dozens of federal agencies, and corporate giants like Airbus and BP. From AI to counterterrorism to climate change to immigration to financial fraud to the future of warfare, the company is at the nexus of the most critical issues of the twenty-first century. Its CEO, Alex Karp, is a distinctive figure on the global business scene. A biracial Jew who is also severely dyslexic, Karp has built Palantir into a tech giant despite having no background in either business or computer science. Instead, he's a trained philosopher who has become known for his strongly held views on a range of issues and for his willingness to grapple with the moral and ethical implications of Palantir's work. Those questions have taken on added urgency during the Trump era, which has also brought attention to the political activism of Karp's close friend and Palantir cofounder Peter Thiel. In The Philosopher in the Valley, journalist Michael Steinberger explores the world of Alex Karp, Palantir, and the future that they are leading us toward. It is an urgent and illuminating work about one of Silicon Valley's most secretive and powerful companies, whose technology is at the leading edge of the surveillance state." -- Dust Jacket